Sayyid: âThe Stranger Kingâ, Religion and Tradition the Case of Cikoang - Hisyam, Muhamad (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2014)
This article describes the sayyid community in Cikoang, South Sulawesi that for about three centuries enjoyed a high status in the society. Given their religious status the sayyid not only eclipse the commoners in term of religion but also in other realm that was in the political arena. The sayyids are said to have dominated the rulers of Cikoang-Laikang âkingdomâ since the mix marriage of sayyids and the noble women of the âkingdomâ until the modern era. The description is developed under a theoretical framework named the stranger kingship.